2017
DOI: 10.1186/s12888-017-1243-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of associated features and drug treatment between co-occurring unipolar and bipolar disorders in depressed eating disorder patients

Abstract: BackgroundTo examine the differences of associated characteristics and prescription drug use between co-occurring unipolar and bipolar disorders in patients with eating disorders (EDs).MethodsPatients with EDs and major depressive episode (MDE) were recruited from psychiatric outpatient clinics. They were interviewed and completed self-administered measures assessing eating and general psychopathology. The prescribed drugs at the index outpatient visit were recorded. Clinical characteristics and prescription d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Antipsychotic agents are known to be associated with obesity, 44 even though other studies have reported that about 40% of drug-naïve BD patients were OB or overweight. 37 As BD-I patients are more likely to be treated with antipsychotic agents/mood stabilizers compared to BD-II patients, 45 in our sample the higher prevalence of a BD-I diagnosis in MDE-OB patients in comparison to a BD-II diagnosis could have been related to the psychotropic medications. However, there are insufficient data to define how much psychotropic treatment is associated with overweight in BD patients.…”
Section: Discussionmentioning
confidence: 75%
“…Antipsychotic agents are known to be associated with obesity, 44 even though other studies have reported that about 40% of drug-naïve BD patients were OB or overweight. 37 As BD-I patients are more likely to be treated with antipsychotic agents/mood stabilizers compared to BD-II patients, 45 in our sample the higher prevalence of a BD-I diagnosis in MDE-OB patients in comparison to a BD-II diagnosis could have been related to the psychotropic medications. However, there are insufficient data to define how much psychotropic treatment is associated with overweight in BD patients.…”
Section: Discussionmentioning
confidence: 75%
“…BMI values for the HC were not consistently reported but for the 18 studies that did, the mean BMI was 21.4 (Table 1). 19 of the studies exclusively included female participants, with the exception of the mixed gender groups in five studies [36,[39][40][41][42]. Zegarra-Valdivia and Chino-Vilca [43] did not specify the genders of their sample.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 25 studies examining WM capacity in AN across 14 countries, 19 of which were case versus control studies and formed the main analysis. The remaining six studies examined WM within AN-R [ 33 , 34 ], pre-and post-recovered AN [ 35 ], comorbid and medicated ED [ 36 , 37 ] or did not perform statistical comparisons between the clinical ED and non-clinical HC groups [ 38 ] (Table 3 ). The combined sample size included 850 AN participants with a mean age of 23 years and a mean BMI of 15.7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations